The Ethnomathematical Concept of Sundanese Local Wisdom through Building Space for the Earth Alit Kabuyutan West Java Site as the Development of Mathematics Learning Media - Emas Marlina; Fadli Azis (Research Collaboration Community (RCC), 2023)
This research is motivated by the preservation of Sundanese culture in West Java which must be instilled in students through learning mathematics and students' mathematical understanding abilities. Based on this problem, an ethnomathematical-oriented learning media device for Sundanese local wisdom was developed through the spatial construction of the Bumi Alit Kabuyutan Site. The purpose of this study was to find out what types of buildings can be used as learning media for mathematics in Geometri and produce valid, practical, and effective mathematics learning media tools for the preservation of Sundanese culture as well as students' mathematical understanding abilities. The research method used is a mixed, namely the Plomp development method and the experimental method. The subjects in this study were class VIII Junior High School Bakti Nusantara in Bandung, West Java, with the sample consisting of 3 classes, namely the limited trial class, the control class, and the experimental class. The research instruments used include validation sheets, student activity observation sheets, implementation sheets of learning media devices, and student response questionnaires, and data collection techniques used include observation, interviews, and questionnaires. The ability of students' mathematical understanding of the geometrical material was measured using a student's mathematical understanding ability test. Data were analyzed by normality, homogeneity, and One Way ANOVA using SPSS. The results showed that (1) the resulting learning tools were valid, practical and effective, (2) the results of the One Way ANOVA test obtained a p-value 0.003 (sig < 0.05) value which indicates that the implementation of the developed learning tools has a significant effect. significant to the preservation of Sundanese culture and the ability of students' mathematical understanding.